2010
DOI: 10.1002/jcp.22317
|View full text |Cite
|
Sign up to set email alerts
|

Possible regulation of trehalose metabolism by methylation in Saccharomyces cerevisiae

Abstract: The current study was undertaken to correlate post-translational protein modification by methylation with the functionality of enzymes involved in trehalose metabolism in Saccharomyces cerevisiae. Trehalose is an economically important disaccharide providing protection against various kinds of stresses. It also acts as a source of cellular energy by storing glucose. Methyl group donor S-adenosyl L-methionine (AdoMet) and methylation inhibitor-oxidized adenosine (AdOx) were used for the methylation study. AdoMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…So far, the acetylproteome of S. cerevisiae has not been analyzed, but several lines of evidence suggest that the extent and relevance of protein acetylation in regulating yeast metabolism may be akin to S. enterica and mammalian cells (Lin et al, 2008(Lin et al, , 2009. The role of methylation in modulating yeast metabolic activity has been, indeed, only documented for three enzymes involved in trehalose metabolism (Sengupta et al, 2011). Among these, they detected acetylation in the gluconeogenic enzyme phosphoenolpyruvate carboxykinase (Pck1) and verified that acetylation of Pck1 at Lys514 is required to assure maximal enzyme activity.…”
Section: Reversible Ptms Affecting Enzyme Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the acetylproteome of S. cerevisiae has not been analyzed, but several lines of evidence suggest that the extent and relevance of protein acetylation in regulating yeast metabolism may be akin to S. enterica and mammalian cells (Lin et al, 2008(Lin et al, , 2009. The role of methylation in modulating yeast metabolic activity has been, indeed, only documented for three enzymes involved in trehalose metabolism (Sengupta et al, 2011). Among these, they detected acetylation in the gluconeogenic enzyme phosphoenolpyruvate carboxykinase (Pck1) and verified that acetylation of Pck1 at Lys514 is required to assure maximal enzyme activity.…”
Section: Reversible Ptms Affecting Enzyme Functioningmentioning
confidence: 99%
“…N-methylation is a frequent, irreversible PTM modifying mainly histones and proteins involved in translational processes (Walsh et al, 2005;Walsh, 2006), though it has not been found to impact metabolic enzymes post-translationally (Pang et al, 2010). The role of methylation in modulating yeast metabolic activity has been, indeed, only documented for three enzymes involved in trehalose metabolism (Sengupta et al, 2011). In their study, they showed that trehalose synthase (Tps1) is subjected to S-methylation in a cysteine residue by formation of a thiol ester, which enhances Tps1 activity.…”
Section: Reversible Ptms Affecting Enzyme Functioningmentioning
confidence: 99%
“…To date, no TPP gene or domain has been identified in nematodes; it is possible that nematodes may synthesize endogenous trehalose using unspecific phosphatases ( Sengupta et al, 2011a , b ; Hespeels et al, 2015 ). Trehalose is suggested to be a signalling molecule, as well as a bioprotective molecule ( Hespeels et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most eukaryotes, trehalose is catalysed by three trehalose metabolism enzymes. Trehalose-6-phosphate synthase (TPS) ( Vandesteene et al, 2010 ; Li et al, 2011 ; Sengupta et al, 2011a , b ; Delorge et al, 2015 ) and trehalose-6-phosphate phosphatase (TPP) ( Ponnu et al, 2011 ; Vandesteene et al, 2012 ; Lahiri et al, 2014 ; Yadav et al, 2014 ) are responsible for trehalose synthesis ( Avonce et al, 2010 ); trehalase (TRE) catalyses the hydrolysis of trehalose ( Pellerone et al, 2003 ; Hespeels et al, 2015 ), and regulates the concentration of sugars ( Alabran et al, 1983 ; Behm, 1997 ). It has been reported that trehalose hydrolysis is catalysed by two types of TRE, acid TRE (AT; Dmitryjuk and Zółtowska, 2003 ) and neutral TRE (NT; Londesborough and Varimo, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation